The Multi-Criteria Decision Model using ANP approach for selection ERP Software of SMEs in the Upper North Region of Thailand - Pakinee Ariya (2020)
© 2020 IEEE. This research aims to present a model of a multi-criteria decision using ANP method that initially and vitally deals with the problems in selecting a suitable Enterprise Resource Planning (ERP) focus on SMEs in the Upper North Region of Thailand. The researcher, in order to demonstrate a knowledge elicitation step, 23 companies from upper North Region of Thailand to collect data and elaborate them using descriptive and analytical approaches with a focus on selecting a suitable ERP software using related theoretical and practical approaches that are identified and reviewed using their own definitions and differences. This research also contains practical/statistical findings that were collected from different ERP consultancies to create a decision-making supporting system that automates an ERP selection process using quantitative analyses of fundamental ERP selection criteria within different classifications.